Literature Review: Factor Analysis of Completeness and Quality of Nursing Care Documentation - Arum Dwi Ningsih (Journal of Ners and Midwifery, 2023)
A problem that often arises in Indonesia is that there are still many nurses who do not carry out maximum documentation. Nurses assume that service to patients is more important than documenting nursing care. The purpose of the literature review was to analyze factors that influence the completeness and quality of nursing care documentation. The protocol in this study used The Center for Review and Dissemination and the Joanna Briggs Institute Guideline as a guide in assessing the quality of the studies that will be summarized. Evaluation of the Literature Review used the PRISMA Checklist to determine the selection of studies that had been determined and adjusted to the objectives of the Systematic Review. The results of the literature review showed that there were 11 journals that discuss factors that influence the quality of nursing care documentation. The results of literature analysis showed that the completeness and quality of nursing care documentation was influenced by internal and external factors. The research results show that attitudes, rewards, workload, motivation and training have been attended.